2008
DOI: 10.1269/jrr.07092
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenol C60(OH)24 Effects on Antioxidative Enzymes Activity in Irradiated Human Erythroleukemia Cell Line

Abstract: Radiotherapy-induced toxicity is a major dose-limiting factor in anti-cancer treatment. Ionizing radiation leads to the formation of reactive oxygen and nitrogen species (ROS/RNS) that are associated with radiation-induced cell death. Investigations of biological effects of fullerenol have provided evidence for its ROS/RNS scavenger properties in vitro and radioprotective efficiency in vivo. Therefore we were interested to evaluate its radioprotective properties in vitro in the human erythroleukemia cell line.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 20 publications
0
43
0
4
Order By: Relevance
“…[14][15][16][17] Polyhydroxylated fullerenes, also known as fullerols [C 60 (OH) n ], belong to a group of antioxidant nanoparticles that exhibit strong antioxidant activity in both in vitro and in vivo biological systems. 13 It has been demonstrated that the anti-inflammatory, 18 antiapoptotic, 16,17 radioprotective, 19,20 and neuroprotective effects 21,22 and the enzyme-inhibitory activity of fullerols 13 have been attributed to their ability to scavenge free radicals, such as superoxide anion radical, hydroxy radical, and nitrous oxide radical. It has since been well established that induction of Nrf2-regulated phase II antioxidant enzymes by nutritional or pharmacological intervention is an effective approach to combat the toxicities of ROS and to protect cells against oxidative stress.…”
Section: Ye Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Polyhydroxylated fullerenes, also known as fullerols [C 60 (OH) n ], belong to a group of antioxidant nanoparticles that exhibit strong antioxidant activity in both in vitro and in vivo biological systems. 13 It has been demonstrated that the anti-inflammatory, 18 antiapoptotic, 16,17 radioprotective, 19,20 and neuroprotective effects 21,22 and the enzyme-inhibitory activity of fullerols 13 have been attributed to their ability to scavenge free radicals, such as superoxide anion radical, hydroxy radical, and nitrous oxide radical. It has since been well established that induction of Nrf2-regulated phase II antioxidant enzymes by nutritional or pharmacological intervention is an effective approach to combat the toxicities of ROS and to protect cells against oxidative stress.…”
Section: Ye Et Almentioning
confidence: 99%
“…In an animal irradiated model that is associated with oxidative stress, pretreatment with C 60 (OH) 24 showed radioprotective effects by scavenging ROS and increasing the antioxidant enzyme activities. 19,20 It has also been reported that C 60 (OH) 24 shows hepatoprotective effects in doxorubicin-treated rats by acting as an antioxidant. 44,45 Hence, it is possible to propose that C 60 (OH) 24 pretreatment prevented deleterious effects of ROS by direct ROS scavenging or increasing the antioxidant enzyme activities.…”
mentioning
confidence: 96%
“…X-ray of high dose (24 Gy) lowered the cell viability of human erythroleukemia K562 cells, C60(OH)24 decreased the effect. Moreover, the cell survival of C60(OH)24-incubated group without the irradiation was higher than that of control group [39]. With the irradiation of lower dose X-ray (2 Gy), 10µM C60(OH)24 did not enhance obviously the cell survival.…”
Section: Radical Scavenger: Protect Cells From the Radiationmentioning
confidence: 79%
“…After being subjected to surface modifications, such nanoparticles demonstrate great promise as de novo therapeutics and mitigators of cytotoxicity. For example, hydroxyl-functionalized C 60 can protect mitochondria from superoxide, hydroxyl, and lipid radicals [29] by enhancing the activities of superoxide dismutase and glutathione peroxidase, effectively reducing oxidative stress [30]. Water-soluble, immunoconjugate C 60 can effectually target the gp240 antigen in human melanoma cells, illustrating the potential of fullerene-based immunotherapeutics for the treatment of cancer [31].…”
Section: Antitumor Metallofullerenol Nanodrugsmentioning
confidence: 99%